Gambaran Fungsi Ginjal Pasien PJK dengan Oklusi Total Kronik yang Menjalani IKP di RSUP Prof. Dr. R. D. Kandou Manado Periode Januari-Desember 2022 - Anjani, Ni Made; Panda, Agnes L.; Jim, Edmond L. (Medical Scope Journal, 2025)
Abstract: Accumulation of fat on the walls of blood vessels can affect blood flow to the heart muscles which has an impact on heart and kidney functions. This study aimed to obtain the description of kidney function in patients with coronary artery disease (CAD) with chronic total occlusion (CTO) who underwent percutaneous coronary intervention (PCI). This was a retrospective and descriptive study with a cross-sectional design. Samples were CAD patients with CTO registered in medical records of Prof. Dr. R. D. Kandou Hospital from January to December 2022. The results showed that there were 95 cases of CTO who underwent PCI. There were 36 (37.9%) patients with increased creatinine levels and decreased eGFR including 33 (34.7%) males, 20 (43.5%) aged 45-59 years, seven (7.4%) with hypertension. There were six patients (16.7%) with contrast induced nephropathy (CIN) including five (13.9%) males, three (8.3%) aged ≥70 years, and two (5.6%) with dyslipidemia. In conclusion, elevated creatinine levels and decreased eGFR are more common in males, pre-elderly, and with hypertension, meanwhile contrast induced nephropathy is more common in males, high-risk elderly, and with dyslipidemia as comorbid. Keywords: kidney function; coronary heart disease; chronic total occlusion; percutaneous coronary intervention   Abstrak: Penumpukan lemak pada dinding pembuluh darah dapat memengaruhi aliran darah ke otot jantung yang berdampak pada fungsi jantung dan ginjal. Penelitian ini bertujuan untuk mengetahui gambaran fungsi ginjal pasien penyakit jantung coroner (PJK) dengan oklusi total kronik (OTK) yang menjalani intervensi koroner perkutan (IKP). Jenis penelitian ialah deskriptif retrospektif dengan desain potong lintang. Sampel penelitian ialah pasien PJK dengan OTK yang tercatat di Rekam Medik RSUP Prof. Dr. R. D. Kandou Manado periode Januari-Desember 2022. Hasil penelitian mendapatkan 95 kasus OTK yang menjalani IKP. Terdapat 36 (37,9%) mengalami peningkatan kadar kreatinin dan penurunan eGFR di antaranya 33 (34,7%) laki-laki, 20 (43,5%) berusia 45-59 tahun, tujuh (7,4%) dengan hipertensi. Terdapat enam pasien (16,7%) yang mengalami contrast induced nephropathy (CIN) diantaranya lima (13,9%) laki-laki, tiga (8,3%) berusia ≥70 tahun, dan dua (5,6%) dengan dislipidemia. Simpulan penelitian ini ialah peningkatan kadar kreatinin dan penurunan eGFR sering terjadi pada laki-laki, kelompok pra lanjut, dengan hipertensi sedangkan contrast induced nephropathy sering terjadi pada pasien laki-laki, usia lanjut berisiko tinggi dan penyakit penyerta dislipidemia. Kata kunci: fungsi ginjal; penyakit jantung koroner; oklusi total kronik; intervensi koroner perkutan